GWAS in Gestational Diabetes Mellitus: Research Advances - Zhou Dikun (BIO Web of Conferences)
As a prevalent metabolic disorder arising in pregnancy, gestational diabetes mellitus (GDM) poses substantial risks to maternal and fetal well-being. The development of GDM is substantially influenced by hereditary components, with variations observed across different racial groups. Genome wide association studies (GWAS) are an effective tool that provides new insights into the genetic mechanism of GDM. This review details the current application of GWAS in GDM research. It sums up the identified susceptibility gene loci and their potential functions in the Chinese population with GDM. Moreover, it underscores the importance of independent research. By establishing a relatively comprehensive reference framework, this study intends to enhance the exploration of the genetic basis of GDM, improve the capacity of precise risk assessment, and develop customized treatment strategies in a clinical context.